Optimalisasi Pembelajaran Akidah melalui Model Sosiodrama dalam Memperkuat Karakter Kejujuran Siswa Kelas VIII SMP Negeri 1 Bandung - Syahidin; Bildan Muhammad Sya'ban (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
Nowadays many issues arise related to the weakening of students' character, particularly the character of honesty. Character development has become a crucial aspect of education, especially at the junior high school level. The Merdeka Curriculum plays a significant role in this process, as it focuses more on character education by providing students with the freedom to express themselves as long as their actions have a positive impact. This study aims to examine and explore the optimization of Aqidah learning through the sociodrama model in strengthening students' honesty character. The research employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation studies, with sociodrama serving as the primary source and various relevant articles as secondary sources. The findings indicate that the application of the sociodrama model is highly significant in strengthening students' honesty character, as evidenced by the gradual improvement in students' habits of practicing honesty. It is hoped that this research can provide a positive contribution to the development of more effective learning models and inspire teachers to explore different models to enhance students' character at various educational levels.